2014
DOI: 10.1002/art.38638
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐23 Mediates the Intestinal Response to Microbial β‐1,3‐Glucan and the Development of Spondyloarthritis Pathology in SKG Mice

Abstract: Results. In curdlan-treated SKG mice, arthritis, enthesitis, and ileitis were IL-23 dependent. Enthesitis was specifically dependent on IL-17A and IL-22. IL-23 was induced in the ileum, where it amplified ER stress, goblet cell dysfunction, and proinflammatory cytokine production. IL-17A was pathogenic, while IL-22 was protective against ileitis. IL-22؉CD3؊ innate-like cells were increased in lamina propria mononuclear cells of ileitis-resistant BALB/c mice, which developed ileitis after curdlan injection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 55 publications
8
130
0
4
Order By: Relevance
“…Mice with an activating mutation in the SH2 domain of this molecule develop axial and peripheral arthritis, which is suppressed in the absence of IL17. Furthermore, studies in SKG mice (ZAP-70 knockout model) have demonstrated that the development of the joint, bone, entheseal, and dactylitic inflammation in these mice is IL23 mediated [25]. Thus, emerging data in animal models implicate an important role for the IL17/IL23 axis in the pathophysiology of psoriasis, enthesitis, synovitis, and abnormal bone turnover in PsA.…”
Section: Il23 and Psoriatic Arthritismentioning
confidence: 99%
“…Mice with an activating mutation in the SH2 domain of this molecule develop axial and peripheral arthritis, which is suppressed in the absence of IL17. Furthermore, studies in SKG mice (ZAP-70 knockout model) have demonstrated that the development of the joint, bone, entheseal, and dactylitic inflammation in these mice is IL23 mediated [25]. Thus, emerging data in animal models implicate an important role for the IL17/IL23 axis in the pathophysiology of psoriasis, enthesitis, synovitis, and abnormal bone turnover in PsA.…”
Section: Il23 and Psoriatic Arthritismentioning
confidence: 99%
“…In the SKG model, mice develop peripheral and axial arthritis, unilateral uveitis, ileitis and psoriasis like skin inflammation in response to intraperitoneal injection of β-1,3-glucan [40]. The severity of peripheral arthritis, spondylitis and enthesitis is significantly reduced in IL-17A−/− SKG mice and SKG mice treated with anti-IL-23 [41].…”
Section: Evidence From Murine Models Of Pso and Psamentioning
confidence: 95%
“…(191). An intestinal Th17 response has been shown to trigger inflammatory arthritis with bony spur formation in a spondyloarthritis mouse model (208). Thus the NLRP family are a potential link between innate inflammation and Th17 induced bone formation in AS.…”
Section: Resultsmentioning
confidence: 99%